2008
DOI: 10.1016/j.geomphys.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Are vortex numbers preserved?

Abstract: We study noncommutative vortex solutions that minimize the action functional of the Abelian Higgs model in 2-dimensional noncommutative Euclidean space. We first consider vortex solutions which are deformed from solutions defined on commutative Euclidean space to the noncommutative one. We construct solutions whose vortex numbers are unchanged under the noncommutative deformation. Another class of noncommutative vortex solutions via a Fock space representation is also studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We note that the relation between these noncommutative instantons and deformed solutions from the commutative ADHM construction [12] is unknown. 2 In the paper [9], we constructed a noncommutative vortex solution which is a deformation of Taubes's vortex solution and showed that its vortex number is undeformed, i. e. independent of the deformation parameter. It is therefore natural to construct a deformed instanton solution via the ADHM construction from the commutative one and to see if the corresponding instanton number is deformed.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the relation between these noncommutative instantons and deformed solutions from the commutative ADHM construction [12] is unknown. 2 In the paper [9], we constructed a noncommutative vortex solution which is a deformation of Taubes's vortex solution and showed that its vortex number is undeformed, i. e. independent of the deformation parameter. It is therefore natural to construct a deformed instanton solution via the ADHM construction from the commutative one and to see if the corresponding instanton number is deformed.…”
Section: Introductionmentioning
confidence: 99%
“…(See, for example, [7,46,47].) Another method to construct noncommutative instantons as smooth deformations of commutative instantons was provided in [48,49,50]. The correspondence between the smooth deformation and the ADHM construction are discussed in [51].…”
Section: B Noncommutative U (1) Instanton In the Fock Spacementioning
confidence: 99%
“…g (l) l . As we see in [12] and Appendix C, g † ⋆ g = I is equivalent to an infinite hierarchy of algebraic equations which we can solve recursively starting with the 0 term. The Laplacian is defined by [15].…”
Section: Notations Definitions and Known Factsmentioning
confidence: 99%
“…On the other hand, we have constructed previously new noncommutative deformations of solitons in gauge theories. These deformations smoothly connect a commutative soliton to a noncommutative soliton [1,12,13]. In the following, we call these smooth noncommutative deformed instantons SNCD instantons for short.…”
Section: Introductionmentioning
confidence: 99%